MAJOR CONFLICT OF GREAT EXPECTATIONS BY CHARLES DICKENS - Aljaidy, Mohammad Zidane; Zamzami, Muhammad Iqbal; Ramadhani, Rahmat Hidayat; Rohmana, Wahyu Indah Mala (CALL, 2024)
This study examines the primary conflicts within the novel Great Expectations, each paragraph focusing on a distinct conflict present in the narrative. The analysis applies Lewis A. Coser's theory of social conflict (2002), which categorizes conflicts into three types: conflicts concerning social statuses, conflicts of interest, and conflicts of role. The objective of this research is to identify these social conflicts within the novel and explore their impact on readers. The study identifies a total of 13 instances of social conflict: 7 related to conflicts concerning social statuses, 3 involving conflicts of interest, and 3 concerning conflicts of role. Employing a descriptive qualitative method, the research analyzes textual data to uncover these conflicts, which are integral to the story of the main character. The novel adopts a mode that combines personal narrative with written and spoken dialogue. The influence of these social conflicts on readers is significant, as they resonate with real-life situations, helping readers to understand and navigate various types of conflicts encountered in everyday life. Keyword: literature, conflict, character